Helicobacter pylori treatment - a review - Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech; Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin (Journal of Education, Health and Sport, 2023)
In this review, current methods of treating Helicobacter pylori bacterial infection are discussed. H. pylori is one of the most common pathogens causing gastrointestinal discomfort. It is considered a major cause of peptic ulcer disease, stomach and duodenal cancer, and MALT lymphoma. The authors analyzed the results of clinical studies regarding the efficacy of various treatment regimens, such as quadruple therapy, triple therapy, therapy with probiotics, therapy with the addition of phytochemical compounds, and therapy with a single drug. In addition, indications for eradication therapy were discussed. The conclusions of the review indicate the need for an individualized approach to the treatment of H. pylori infection, taking into account the rapidly increasing antibiotic resistance and patient risk factors for eradication.